Fossil mammals of Asia : Neogene biostratigraphy and chronology - Wang, Xiaoming, 1957-; Flynn, Lawrence J. (Lawrence John), 1932-; Fortelius, Mikael (Columbia University Press, 2013)
"This book is on the emergence of mammals in Asia, based largely on new fossil finds throughout Asia and cutting-edge biostratigraphic and geochemical methods of dating the fossils and their geological substrate"--Provided by publisher